Mismatched filter for transmit waveform with frequency notches - Liu, Aifei (2018)
In order to reduce radar interference on communication systems within shared bands, the radar transmit waveform forms frequency notches in the shared bands. However, because of the notches, the auto-correlation of the transmit waveform with frequency notches leads to high-range sidelobes. In order to achieve low-range sidelobes, the authors propose a mismatched filter. The mismatched filter for the transmit waveform with frequency notches has the same range sidelobes as the auto-correlation of the transmit waveform without frequency notches at the expense of a signal-to-noise ratio (SNR) loss. Simulation and analysis results demonstrate that the proposed mismatched filter always has low sidelobes at the cost of a SNR loss. In addition, simulation results show that the SNR loss is acceptable even for the deep notches (i.e. 20 dB), when the ratio of the waveform energy in the shared bands to the total waveform energy is moderate (i.e. <;8%). However, the SNR loss increases rapidly with the depth of notches, when the ratio is large.